2010
DOI: 10.1007/s00330-010-1792-9
|View full text |Cite
|
Sign up to set email alerts
|

Coronary artery stent imaging with 128-slice dual-source CT using high-pitch spiral acquisition in a cardiac phantom: comparison with the sequential and low-pitch spiral mode

Abstract: The HPS mode of 128-slice dual-source CT yields fewer artefacts inside the stent lumen compared with SPIR and SEQ, but image noise is higher. ALN is still too high for routine stent evaluation in clinical practice. Radiation dose of the HPS mode is markedly (less than about tenfold) reduced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 26 publications
0
13
1
Order By: Relevance
“…Previous reports concluded that the stents less than 3 mm in diameter couldn't be interpretated by 64-MDCT, 256-slice MDCT, even with dual source CT [9,[18][19][20]. In the present study, with an improved spatial resolution of 0.23 mm, we were able to observe the stents lumen with 2.75 mm and more in diameter clearly.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…Previous reports concluded that the stents less than 3 mm in diameter couldn't be interpretated by 64-MDCT, 256-slice MDCT, even with dual source CT [9,[18][19][20]. In the present study, with an improved spatial resolution of 0.23 mm, we were able to observe the stents lumen with 2.75 mm and more in diameter clearly.…”
Section: Discussioncontrasting
confidence: 51%
“…Previous studies using standard resolution CT have shown that the stent lumen is limited by blooming artifacts, which are more significant in stents ≤3 mm in diameter, even in novel 64-slice multi-detector single-and dual-source CT systems, which offer isotropic voxel resolution up to 0.4 mm [5][6][7][8][9]. Therefore, the spatial resolution is a key factor in the imaging of coronary artery stent and needs to be further improved from the standard resolution CT system for the stent lumen visualization.…”
Section: Introductionmentioning
confidence: 99%
“…Potentially, CTP may solve another limitation of CTA, the detection of in-stent restenosis 19 (Figure 2), which has a sensitivity and specificity of 79% and 81%, respectively, 19 because of artifacts from stent struts causing variable (44% to 48%) artificial luminal narrowing. 20 Second, in patients presenting with intermediate stenosis of 50% to 70% on coronary CTA, an MPI study (CMR, SPECT, or ECG-treadmill) is required to determine whether a post-IA is necessary. In these patients, the addition of an adenosine stress CTP examination may provide this information while adding only little time and efforts for the patient and physician.…”
Section: Discussionmentioning
confidence: 99%
“…Considerable problems continue to be present for the CT imaging of coronary artery stents. While CT stent imaging can be now performed -similar to the imaging of the native coronary arteries -at a low radiation dose, the in-stent visualization still is limited [30,31], and a routine application of CT for the follow-up of coronary stent patency cannot be recommended so far.…”
Section: Outlook and Conclusionmentioning
confidence: 99%